Russia and Azerbaijan: A Borderland in Transition by Tadeusz: Swietochowski, Columbia University Press, 1995. (American Journal of Islam and Society, 1997)
The last centuries of human history bear witness to the generation of havocand carnage brought about by the disintegration of world empires and superpowersthat ruled vast areas inhabited by people of different ethnic. religious,and national backgrounds. One such event took place in the early period of thiscentury: the collapse of the Ottoman Empire. Its downfall left a power vacuumin many areas of the Balkans. North Africa and the Middle East. Out of the ashesof its ruin, new and independent states emerged.Toward the end of the twentieth century, the Soviet Union totally disintegratedand suddenly disappeared from the international scene in a relatively shorttime. As mentioned. history has recorded the gradual decline and final fall ofgreat empires. The collapse of the Soviet Union differs from other olderempires. We will draw a comparison between its disintegration and the fall ofthe older Ottoman Empire.There are abundant scholarly and literary analyses indicating that the OttomanEmpire underwent a process of gradual dismantling from it initial decline to itsfinal collapse. The Soviet Union, however, underwent an abrupt end to its reignand. entered ultimate oblivion without experiencing a prolonged loss of vitality.This abrupt fall and quick end may be auributed to various factors, from the failureof economic policies to the yearning for freedom. including the revival ofethnic, religious. and national identities. These are the points emphasized bySwietochowski's timely book on Russia and Azerbaijan.The current wave of world events exerts itself nor only upon the political elitebut also within academic quarters and on publishing trends. As the 1979 Iranianrevolution drew greater attention to Islam and was followed by the establishmentof new departments of Islamic studies and the publication of hundreds ofbooks on the subject, the collapse of the Soviet Union generated a significantamount of interest and, accordingly, academicians and publishing housesresponded to the growing search to know more about the region.Swietochowski's look should be considered a significant contribution to theseeffons.It is a widely held observation thal the disintegration of Lhe Soviet Union dramaticallychanged and traumatized the geopolitical and geocullural landscape ofthe area. Swietochowski's book concentrates specifically on Azerbaijan byexamining closely the last two centuries of this unknown land's history. As thetitle Russia and Azerbaijan: A Borderland in Transition suggests, the authordeals with a people whose land is divided between north and south. He usesarchival sources, official documents, and numerous books and articles written invarious languages to inform readers about a land and a people about which littlewas known before the Soviet Union's downfall. Swietochowski's work ...